Assessment of customer satisfaction on tqm practices in Oman’s construction industry - Ali, Khalid; Bakar, Abu Hassan Abu (2008)

(untitled)
Customer satisfaction considered as the one of the key factors of the basic concept of quality management. Construction companies are competing to implement specific strategies, principles and norms of quality management to raise the level of quality in the Constructions sector to satisfy clients who are the owner of projects. Some of these companies resort to measure customers satisfaction level with a view to identify existing weakness of these companies, taking the opinion of the clients in mind so as to limit or reduce these shortcomings. This paper aims to highlight the view of the clients towards construction industries and the existing variables in these construction organizations in Oman. Such variables are administrative, project management, construction and logistical, according to the category of each company. In addition to that, the focus of this paper is to highlight the different views by customers to each category, questionnaires were distributed to some 300 clients of projects to gauge their views towards contractors, the results were analyzed by using T-test method. The finding of this study is that there was unhappiness by clients towards the first and third grades contractors, but they are satisfied in general.